1993
DOI: 10.1148/radiology.189.2.8210364
|View full text |Cite
|
Sign up to set email alerts
|

Irradiation of the cervix uteri: value of unenhanced and contrast-enhanced MR imaging.

Abstract: Overall, diagnosis was best with unenhanced T2-weighted images, but in patients with adnexal or pelvic sidewall recurrence and in patients with treatment complications (eg, fistula formation), contrast enhancement did help.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
49
0
2

Year Published

1997
1997
2015
2015

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 84 publications
(52 citation statements)
references
References 0 publications
1
49
0
2
Order By: Relevance
“…However, the early detection of recurrent disease in the pelvis may pose a diagnostic challenge. The symptoms can be nonspecific, and physical examination of the irradiated pelvis is often limited (3). In addition, cytological examination of the irradiated cervix has a poor sensitivity for detecting tumor recurrence, ranging from 28% to 51% (4,5).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, the early detection of recurrent disease in the pelvis may pose a diagnostic challenge. The symptoms can be nonspecific, and physical examination of the irradiated pelvis is often limited (3). In addition, cytological examination of the irradiated cervix has a poor sensitivity for detecting tumor recurrence, ranging from 28% to 51% (4,5).…”
mentioning
confidence: 99%
“…In a study of patients with cervical cancer treated with radiotherapy, Hricak et al (3) reported that T2-weighted imaging is better than nonenhanced or nondynamic contrastenhanced T1-weighted imaging for detection of tumor recurrence. However, other studies have questioned the accuracy of T2-weighted MR imaging to distinguish between tumor recurrence and posttherapy fibrosis (6 -10).…”
mentioning
confidence: 99%
“…Parametrial fi brosis displaying low SI on T2WI is most evident in areas of previous tumor invasion (Engin 2006 ). Complete reconstitution of the normal cervical anatomy and low SI of cervical stroma indicate tumor-free status (97 % PPV for exclusion tumor recurrence) (Hricak et al 1993 ). However, particularly, within the fi rst 3 months of treatment, differentiation between residual tumor and postirradiation changes is not possible (Engin 2006 ).…”
Section: Cervix and Vaginamentioning
confidence: 99%
“…9 ), but cyclic changes of folliculogenesis may resume. Hydrosalpinx caused by tubal obstruction may be seen after hysterectomy and uterine radiation therapy, both in pre-and postmenopausal age (Hricak et al 1993 ).…”
Section: Ovariesmentioning
confidence: 99%
See 1 more Smart Citation